NMR Provides Unique Insight into the Functional Dynamics and Interactions of Intrinsically Disordered Proteins - Camacho-Zarco, Aldo R; Schnapka, Vincent; Guseva, Serafima; Abyzov, Anton; Adamski, Wiktor; Milles, Sigrid; Jensen, Malene Ringkjøbing; Zidek, Lukas; Salvi, Nicola; Blackledge, Martin (Chemical reviews, 2022)
Intrinsically disordered proteins are ubiquitous throughout all known proteomes, playing essential roles in all aspects of cellular and extracellular biochemistry. To understand their function, it is necessary to determine their structural and dynamic behavior and to describe the physical chemistry of their interaction trajectories. Nuclear magnetic resonance is perfectly adapted to this task, providing ensemble averaged structural and dynamic parameters that report on each assigned resonance in the molecule, unveiling otherwise inaccessible insight into the reaction kinetics and thermodynamics that are essential for function. In this review, we describe recent applications of NMR-based approaches to understanding the conformational energy landscape, the nature and time scales of local and long-range dynamics and how they depend on the environment, even in the cell. Finally, we illustrate the ability of NMR to uncover the mechanistic basis of functional disordered molecular assemblies that are important for human health.
Keywords: Intrinsically Disordered Proteins; Thermodynamics; Humans; magnetická rezonanční spektroskopie; Nuclear Magnetic Resonance, Biomolecular; Protein Conformation; lidé; termodynamika; Magnetic Resonance Spectroscopy; vnitřně neuspořádané proteiny; nukleární magnetická rezonance biomolekulární; konformace proteinů